Amalan Guru Dalam Pengajaran Subjek Maharat Al-quran Kurikulum Bersepadu Tahfiz - Mohd Aderi Che Noh; Sri Andayani Mahdi Yusuf; Khadijah Abdul Razak (USIM Press, 2024)
This study aims to measure the level of teacher practice in teaching the subject of Maharat al-Quran Integrated Curriculum Tahfiz (KBT). A total of 621 teachers were made respondents in this study. This study is in the form of a cross-sectional survey involving teachers from KBT secondary schools throughout Malaysia. While the sampling method of this study uses stratified random sampling method. Data were analyzed using IBM Statistical Package for Social Science (SPSS) software version 25.0 Descriptively to determine the mean value, standard deviation and percentage. The findings of the study show that the level of teacher practice in teaching the subject of Maharat al-Quran KBT is at a high level. In conclusion, this study successfully highlights the uniqueness of the findings that teachers in secondary schools who implement KBT practice well the teaching of tajwid law, manners of the Quran, recitation, knowledge of Qiraat, practice of Qiraat and Rasm Uthmani in the subject of Maharat al-Quran. The science of tajwid is the main teaching emphasized by the teacher to enable students to learn the Quran. The implication is that tahfiz teachers have a role to teach Quranic skills because teachers are the driving force behind a built curriculum.